Phytochemical screening of selected plant species found within UPV Miagao campus. - Demaclid, Stacy Ermo (1998.)
Eleven plant species were subjected to phytochemical screening for alkaloids, flavonoids and saponins. Three plant species (Premna integrifolia, Ocimum tenniflorum and Securinaga virosa) were found positive to all tests. Antimicrobial tests on the ethanolic residues of these plants show that Securinaga virosa exhibited weak antimicrobial activity against S aureus, B, subtilis and Saccharomyces champange. On the other hand, Premna integrifolia exhibited no antimicrobial activity., Sequential solvent extraction on the crude ethanolic residue of Securinaga virosa was done using n-hexane, ethyl acetate, n-butanol and aqueous-methanol (3:1). Antimicrobial test shows that the polar portion is active against S. aureus, B. subtilis and Saccharomyces champange. Column chromatographic separation of the polar portion had produced three fractions. Antimicrobial tests on these fractions show that the most polar column fraction (fraction that came out last from the column) is active against S. aureus and B. subtilis at the minimum inhibitory concentration of 0.80 mg/ml and 1.40 mg/ml respectively. It is also active against Saccharromyces champange. On the other hand, the least polar fraction (the fraction that came out first from the column) is active against P. auregenosa at the minimum inhibitory concentration of 1.20 mg/ml. Preliminary investigation on the TLC-spots of the most polar fraction suggests that it is possibly a flavonoid while the least polar column fraction produced an orange spot when sprayed with Dragendorff's reagent indicating that it is possibly an alkaloid.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Plant Species -- UPV, Miagao